Photochemically Induced Synthesis of the Topoisomerase I Inhibitors Indeno[1,2-c]isoquinoline-5,11-diones - Dubois, Mélanie; Deniau, Eric; Couture, Axel; Grandclaudon, Pierre (Synlett, 2012)
A convenient synthesis of indeno[1,2-c]isoquinoline-5,11-diones has been achieved using combinational photochemical and carbocationic cyclization tactics. The synthetic route involved first the construction of adequately functionalized N-styryl benzamides via Suzuki–Miyaura cross-coupling reaction with enol phosphate combined with a six-π-electron photocyclization process. The assembling of the title compounds was readily ensured through sequential carbocationic annulation reaction and ultimate oxidation of a latent hydroxy functionality.
Keywords: enols; phosphates; cross-coupling; electrocyclic reactions; lactams